A scrap of paper : breaking and making international law during the Great War - Hull, Isabel V. (Cornell University Press, 2014)
A century after the outbreak of the Great War, we have forgotten the central role that international law and the dramatically different interpretations of it played in the conflict's origins and conduct. Hull compares wartime decision making in Germany, Great Britain, and France, weighing the impact of legal considerations in each. Throughout, she emphasizes the profound tension between international law and military necessity in time of war, and demonstrates how differences in state structures and legal traditions shaped the way in which each of the three belligerents fought the war.